Placement of a Canine Mini-trochlear Prosthesis in a Cat with Chronic Patellar Luxation - Hennemann, Carlos Leandro; Borba, Bernardo dos Anjos; Maciel, Mônica; Canever, Ricardo José; Inaba, Charlene Gonçalves; Minto, Bruno Watanabe; Villanova Junior, José Ademar (VCOT Open, 2025)
To report the placement of a trochlear groove prosthesis in a domestic cat with grade 4 medial patellar luxation and severe patellofemoral osteoarthritis using a mini-implant designed for dogs. A 1-year and 9-month-old female cat with left pelvic limb 3/6 grade lameness of 10-month duration was attended at a private veterinary hospital. Physical examination showed marked periarticular thickening, reduced femoral muscle mass, and stifle crepitation. Radiographic changes were consistent with joint effusion, decreased joint space between femoral and tibial medial condyles, and osteophyte on the distal patellar margin. Trochleoplasty was not recommended due to articular deterioration, and the placement of a canine #3 trochlear prosthesis was planned. The base plate was fixed with cortical screws and the trochlear prosthesis was attached through Morse taper abutments. Radiographic follow-ups confirmed the adequate position of both the patella and trochlear prosthesis. After 30 days, the cat presented 1/6 grade lameness and was medically discharged after 60 days. After 2 years, the cat presented normal mobility using a mini-canine trochlear prosthesis. Using a trochlear prosthesis to replace the femoral patellar groove of cats is suggested as a viable strategy to align the extensor mechanism, improve patellar stability, and manage patellofemoral osteoarthritis-induced lameness.
Keywords: patellar luxation; patellar dislocation; trochlear prosthesis; patellar groove; cat